METHODOLOGICAL AND PRACTICAL PROVISIONS OF THE ECONOMIC SECURITY OF THE REGION - SIUTA, Sviatoslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study analyzes the issues of managing the economic security of the region. It is shown that it is a systemic and complex problem that requires a specific approach to the formation and implementation of regional security and economic policy. It is pointed out that despite the presence of a significant range of scientific research results in the field of economic security, a reasoned clarification of the set of components of regional economic security is required, including from the perspective of the specifics of the current state of functioning of national and regional economic systems in Ukraine in conditions of full-scale war. From these positions, the purpose of the study is to generalize and further develop methodological and applied provisions of the economic security of the region. The imperatives of transformation in the system and guidelines for ensuring the economic security of the region at different stages of economic development are determined by the following components, as the level of security, the nature of the impact of danger, threats to sustainable development, strategic guidelines for ensuring security, relevant regulatory mechanisms. It is argued that such phases of the economic cycle as recovery and boom are characterized by a higher level of economic security of the region and, accordingly, a smaller spectrum and severity of challenges and threats. And vice versa: phases of recession and depression are their actualization, aggravation and intensification of the issues of ensuring security. However, in our opinion, we can state with all confidence that security problems can also be characteristic of stages of recovery and economic boom in the event of an insufficient level of control over the course of macroeconomic processes. Accordingly, the threats of the formation of an irrational structure of the regional economy with the consequences of the so-called unsustainable development, the emergence of various kinds of distortions and deformations, market "bubbles", etc., which will lay the foundations for further probable destabilization of the situation in the socio-economic system of the "region", undermining its stability and resilience, may be relevant at the growth stage.